A meta‐analysis of the association between Helicobacter pylori (H. pylori) infection and hyperemesis gravidarum. Issue 1 (26th November 2017) - Ng, Qin Xiang; Venkatanarayanan, Nandini; De Deyn, Michelle Lee Zhi Qing; Ho, Collin Yih Xian; Mo, Yin; Yeo, Wee‐Song
Abstract: Background: Hyperemesis gravidarum remains a common, distressing, and significant yet poorly understood disorder during pregnancy. The association between maternal Helicobacter pylori ( H. pylori ) infection and hyperemesis gravidarum has been increasingly recognized and investigated. This study thus aimed to provide an updated review and meta‐analysis of the topic. Methods: Using the search terms ( H. pylori OR Helicobacter OR Helicobacter pylori OR infection) AND (pregnancy OR emesis OR hyperemesis gravidarum OR nausea OR vomiting), a preliminary search on the PubMed, Ovid, Web of Science, Google Scholar, and WanFang database yielded 372 papers published in English between January 1st, 1960 and June 1st, 2017. Results: A total of 38 cross‐sectional and case‐control studies, with a total of 10 289 patients were eligible for review. Meta‐analysis revealed a significant association between H. pylori infection and hyperemesis gravidarum during pregnancy, with a pooled odds ratio of 1.348 (95% CI: 1.156‐1.539, P  < .001). Subgroup analysis found that serologic and stool antigen tests were comparable methods of detecting H. pylori as they yielded similar odds ratios. Limitations: Although the studies did not have high heterogeneity ( I 2  = 28%), publication bias was observed, and interstudy discrepancies in the diagnostic criteria adopted for hyperemesis gravidarum limit the reliability of findings. Also, 15 of the included studies were from the same country (Turkey), which could limit the generalizability of current findings. The prevalence of H. pylori infection varies throughout the world, and there may also be pathogenic differences as most strains of H. pylori in East Asia carry the cytotoxin‐associated gene A gene. Conclusion: H. pylori infection was associated with an increased likelihood of hyperemesis gravidarum during pregnancy. Given the high prevalence of H. pylori infections worldwide, detecting H. pylori infection and the eradication of maternal H. pylori infection could be part of maternal hyperemesis gravidarum management. Further confirmation with robust longitudinal studies and mechanistic investigations are needed.